1994
DOI: 10.1007/bf00666056
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of weekly mitoxantrone, 5-fluorouracil, and leucovorin in metastatic breast cancer

Abstract: A phase II study to test the toxicity and the efficacy of a weekly combination of Mitoxantrone, 5-Fluorouracil and L-Leucovorin (MFL) was carried out in 43 patients with metastatic breast cancer. Chemotherapy consisted of mitoxantrone 4 mg/m2, 5-fluorouracil 375 mg/m2, and L-leucovorin 100 mg/m2 on day 1, weekly. Patient characteristics were: median age 53 years (range 36-65); estrogen receptor (ER) status was known in 26 patients and of these 15 (57.7%) patients were ER-positive and 11 (42.3%) ER-negative. Of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…However, it must be noted that the comparison of results achieved in small groups of patients is biased by uncontrollable differences in patient selection. Repetto et al [25] evaluated a weekly regimen consisting of mitoxantrone, 5-fluorouracil, and leucovorin in 43 metastatic patients, obtaining a response rate of 28.2% with a median response duration of 12 months (range 6-34). Furthermore, Swain et al [26] reported an overall response rate of 33% in 15 evaluable pretreated patients.…”
Section: Discussionmentioning
confidence: 98%
“…However, it must be noted that the comparison of results achieved in small groups of patients is biased by uncontrollable differences in patient selection. Repetto et al [25] evaluated a weekly regimen consisting of mitoxantrone, 5-fluorouracil, and leucovorin in 43 metastatic patients, obtaining a response rate of 28.2% with a median response duration of 12 months (range 6-34). Furthermore, Swain et al [26] reported an overall response rate of 33% in 15 evaluable pretreated patients.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, a phase II study showed that the regimen of weekly mitoxantrone, 5-fluorouracil, and leucovorin (MFL) was well tolerated and moderately effective to treat MBC [89]. And a phase 3 trial of eniluracil +5-fluorouracil+leucovorin in MBC is also ongoing [90].…”
Section: Discussionmentioning
confidence: 99%